2016
DOI: 10.1111/jcpp.12656
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for children and adolescents with behavioural and emotional problems: a randomised controlled trial

Abstract: Background: Although music therapy (MT) is considered an effective intervention for young people with mental health needs, its efficacy in clinical settings is unclear. We therefore examined the efficacy of MT in clinical practice. Methods: Two hundred and fifty-one child (8-16 years, with social, emotional, behavioural and developmental difficulties) and parent dyads from six Child and Adolescent Mental Health Service community care facilities in Northern Ireland were randomised to 12 weekly sessions of MT pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 33 publications
5
88
0
3
Order By: Relevance
“…Therapists confirmed that 13-year olds tended to be more open towards GMT, whereas 15-year olds were more inclined towards choosing their peers independently. In contrast, individual music therapy was found to be more beneficial for older participants (Porter, et al, 2015). Finally, previous findings on dose-effect relations (Gold, et al, 2009) and minimum effective numbers of sessions (Mössler, et al, 2011) might suggest eight sessions of GMT were too short.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therapists confirmed that 13-year olds tended to be more open towards GMT, whereas 15-year olds were more inclined towards choosing their peers independently. In contrast, individual music therapy was found to be more beneficial for older participants (Porter, et al, 2015). Finally, previous findings on dose-effect relations (Gold, et al, 2009) and minimum effective numbers of sessions (Mössler, et al, 2011) might suggest eight sessions of GMT were too short.…”
Section: Discussionmentioning
confidence: 75%
“…Fewer researchers have focused on adolescents specifically, yet evidence suggests some effectiveness for adolescents with various psychopathologies (Albornoz, 2011;Gold, Voracek, & Wigram, 2004). For example, improvisational music therapy may improve communication and interaction skills, self-esteem and depressive symptoms in adolescents with behavioral and emotional problems (Porter, McConnell, McLaughlin, Lynn, & Holmes, 2015). Authors of qualitative studies and clinical reports have described preventive music therapy approaches, often targeting person-centered benefits related to emotion and peer connectedness Jacobsen & Killen, 2015;Kim, 2015;Kim et al, 2006;Kruger & Stige, 2015;McFerran, Roberts, & O'Grady, 2010;Viega, 2013).…”
mentioning
confidence: 99%
“…Finally, a separate scale assesses ASD symptoms. It has been used to assess social difficulties among youth with ASD [Gillis, Callahan, & Romanczyk, ], social anxiety [Gresham, Vance, Chenier, & Hunter, ], and behavioral/emotional problem [Porter et al, ]. The internal consistency of the SSIS measures in the current study, calculated at T1, were α = 0.86 for parents and α = 0.91 for teachers.…”
Section: Methodsmentioning
confidence: 79%
“…Studies which link young people and music are diverse and heterogeneous, covering different areas of music, practice and discipline (McFerran, Garrido, & Saarikallio, 2016). Some studies have explored the effectiveness of music interventions in supporting adolescents with psychopathologies (Albornoz, 2011;Gold, Saarikallio, Crooke, & McFerran, 2017;Gold, Voracek, & Wigram, 2004;Gold, Wigram, & Voracek, 2007), whereas others have analysed how these interventions can improve social connectedness and self-esteem among adolescents with mental health problems and behavioural problems (Hense & McFerran, 2017;McFerran et al, 2016;Porter et al, 2017). Researchers | 989 CALÓ et AL. have also considered the role of community-based initiatives promoting arts and music in addressing problems of disadvantaged young people (Harkins, Garnham, Campbell, & Tannahill, 2016;Parker, Marturano, O'Connor, & Meek, 2018), in youth custodial (Daykin, Viggiani, Moriarty, & Pilkington, 2017) and in community settings (Davies et al, 2013).…”
Section: Introductionmentioning
confidence: 99%